Expression and purification of Cry8Da recombinant protein against coleopteran insects of bacillus thuringiensis in E. Coli - Thi Minh Thanh, Le; Thi Hue, Nguyen; Duy Quy, Tran; Dinh Binh, Ngo (Vietnam Journal of Science and Technology, 2017)
Bacillus thuringiensis (Bt) is widely used in agriculture for pest control against Lepidoptera, Diptera and Coleoptera orders. It is very difficult to control of Coleoptera pests such as larvae of Scarabaeidae family, which damage the roots of tusf grass and other horticultural and agricultural plants, because they are living in soil where sprayable insecticidal formulation is hard to reach the target insects. The Cry8-type proteins specified to larvae of scarab beetles. The Cry8-type proteins are insecticidal to larvae of scarab beetles. Bacillus thuringiensis Cry8D (Cry8Da, Cry8Db) insecticidal proteins are unique among Cry8 family protein in terms of its insecticidal activity against larvae and adult Scarab beetles, such as Japanese beetle (Anomala cuprea, Popillia japonica). In this study, cry8Da gene encoding nature protein Cry8Da, which were isolated in Vietnam, was expressed in E. coli. The 2031 bp of cry8Da gene is digested from recombinant plasmid pGEM-cry8Da with BamHI và sacI and ligated into pET32a(+) vector treated with the same enzymes. The recombinant plasmids pET32a(+)-cry8Da were expressed in BL21(DE3)LysS strain under induction of IPTG. The highest level for expression of Cry8Da recombinant E. coli has been obtained after induction by 1 mM IPTG at 30 0C for 4 hrs. Recombinant Cry8Da protein has molecular mass about 96 kDa and purified by Ni(2+) affinity chromatography column, concentration 0,45 mg/ml after purification. The expressed recombinant Cry8Da protein was confirmed by Western blot using anti-Cry8Da antibody.